2006
DOI: 10.1371/journal.pone.0000026
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Oct3/4-Regulated Gene Networks in Embryonic Stem Cells by Expression Profiling

Abstract: POU transcription factor Pou5f1 (Oct3/4) is required to maintain ES cells in an undifferentiated state. Here we show that global expression profiling of Oct3/4-manipulated ES cells delineates the downstream target genes of Oct3/4. Combined with data from genome-wide chromatin-immunoprecipitation (ChIP) assays, this analysis identifies not only primary downstream targets of Oct3/4, but also secondary or tertiary targets. Furthermore, the analysis also reveals that downstream target genes are regulated either po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
189
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(203 citation statements)
references
References 71 publications
13
189
0
1
Order By: Relevance
“…However, it is interesting to observe that in the epidermis, deletion of Akt1 causes thinner epidermal layers and retarded-HF development, whereas double mutants (Akt1 À/À Akt2 À/À and Akt1 À/À Akt3 À/À ) (Peng et al, 2003;Yang et al, 2005) show more severe defects, and transgenic mice expressing Akt-Mer fusion proteins induces epidermal hyperplasia and proliferation of epidermal progenitors leading to epidermal and follicular hyperplasia (Murayama et al, 2007). As already pointed out before, Tcl1 is involved in the normal-self renewal of ES cells (Glover et al, 2006;Matoba et al, 2006;GalanCaritad et al, 2007) and upstream genes such as transcription factor Oct4, which directly activates Tcl1 in ES cells and is expressed in human HFs (Yu et al, 2006), should also be taken into account.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, it is interesting to observe that in the epidermis, deletion of Akt1 causes thinner epidermal layers and retarded-HF development, whereas double mutants (Akt1 À/À Akt2 À/À and Akt1 À/À Akt3 À/À ) (Peng et al, 2003;Yang et al, 2005) show more severe defects, and transgenic mice expressing Akt-Mer fusion proteins induces epidermal hyperplasia and proliferation of epidermal progenitors leading to epidermal and follicular hyperplasia (Murayama et al, 2007). As already pointed out before, Tcl1 is involved in the normal-self renewal of ES cells (Glover et al, 2006;Matoba et al, 2006;GalanCaritad et al, 2007) and upstream genes such as transcription factor Oct4, which directly activates Tcl1 in ES cells and is expressed in human HFs (Yu et al, 2006), should also be taken into account.…”
Section: Discussionmentioning
confidence: 87%
“…If the expression of Tcl1 is maintained constantly within the same cells, as it seems to be in other tissues such as B cells and embryo, it would implicate that proliferating cells that derive from HG-cells, during catagen-telogen transition, are those starting the new HF cycle and repopulating the bulge ( Figure 5). As in the embryo, where Tcl1 is necessary in the first divisions of proliferating cells of the preimplantation embryo, and for self-renewal but not differentiation of their derived ES-cells (Matoba et al, 2006;Galan-Caritad et al, 2007) in the HF, Tcl1 is important very early during the anagen proliferation of secondary HG-cells, as beyond the third day after depilation the expression of Tcl1 is no more detectable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a third group of genes, we obtained reproducible reverse transcriptase-PCR evaluation ( Figure 3). In particular, we detected the expression of OCT3, NANOG and KLF4, which are part of the core transcriptional circuitry for regulation of embryonic stem cell properties (Matoba et al, 2006;Masui et al, 2007). Of great interest is that BRG1 downregulation completely abolished NANOG expression ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the SAGE data, we characterized Trh expression using WISH where we see expression at E6.5 but not at E5.5 (data not shown). Of interest, it has recently been shown that Trh may be a direct transcriptional target of POU5F1, a well-characterized marker of pluripotency in embryonic stem cells and the epiblast (Loh et al, 2006;Matoba et al, 2006). Pou5f1 expression in the epiblast overlaps with that of Trh, suggesting that POU5F1 may in part be regulating Trh expression at this stage (Rosner et al, 1990).…”
Section: Discussionmentioning
confidence: 99%